The doctrine of the “ideal state”: Ibn Rushd and al-Farabi (comparative analysis) - M T Zianshina (RUDN Journal of Philosophy, 2015)
The article attempts to show the evolution of the doctrine of the “ideal state” in the eastern peripatetism, based on a comparative analysis of the treatises of Ibn Rushd “Talhis al-siyasah” and al-Farabi “The Virtuous City”.